Performance improvement of a modified cavity receiver for parabolic dish concentrator at medium and high heat concentration. (October 2020) - Bopche, Santosh; Rana, Kartik; Kumar, Varinder
Graphical abstract: Highlights: Roughened modified cavity receivers with conical protrusions are developed for solar dish. Smooth receiver performance compared with that of roughened receivers. Mathematical analysis simulating one of the experimental test situations is also presented. Abstract: The performances of parabolic dish collector systems depend on the losses encountered during converting solar energy into thermal energy. It encompasses optical losses from the reflector and heat losses through the solar receiver. The geometry and surface properties of the receiver were seen considerably influencing the system performance. Thermally conductive copper fins (conical shaped, tip/cone angle 30°) have been fixed inside the cavity surface for three different pitch values e.g. 12.5 mm, 22 mm and 44 mm. During brazing operation, a selective Copper Oxide (CuO) surface was formed inside of the cavity, on account of heating. The system collection efficiency values obtained using finned cavities were compared with that of smooth (conventional) one. Performance improvement of about 23.56% and 31.35% (on average) over a smooth cavity was noticed after providing conical protrusions on the radiative surface of the modified cavity receiver, with medium and higher heat boundary conditions. The percentage contributions of heat losses by conduction, convection, and radiation modes, from the examined cavities, were obtained as 1.4–3.2%, 70–75%, and 22–28% of the total losses, respectively, in case of medium irradiation concentration. The energy concentration was seen influencing these contributions of heat losses from the receivers. Mathematical analysis is also presented for comparing one of the experimental test situations outcomes.